Test particle comparison of heavy atomic and molecular ion distributions at Mars. Issue 3 (31st March 2014) - Curry, S. M.; Liemohn, M.; Fang, X.; Ma, Y.; Slavin, J.; Espley, J.; Bougher, S.; Dong, C. F.
<x xml:space="preserve">Abstract</x> This study uses the Mars Test Particle simulation to create virtual detections of O+, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5bxvgbf0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2+</alternatives>, and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5bxvgbdf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO2+</alternatives> in an orbital configuration in the Mars space environment. These atomic and molecular planetary pickup ions are formed when the solar wind directly interacts with the neutral atmosphere, causing the ions to be accelerated by the background convective electric field. The subsequent ion escape is the subject of great interest, specifically with respect to which species dominates ion loss from Mars. O+ is found to be the dominant escaping ion because of the large sources of transported ions in the low‐energy (<10 eV) and high‐energy (>1 keV) range. <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5bxvgbjn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2+</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5bxvgbk6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO2+</alternatives> are observed at these energy ranges but with much lower fluxes and are generally only found in the tail between 10 eV and 1 keV. Using individual particle traces, we reveal the origin and trajectories of the low‐energy downtail O+ populations and high‐energy polar O+ populations that contribute to the total escape. Comparing them against <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5bxvgbgj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2+</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5bxvgbh3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO2+</alternatives> reveals that the extended hot oxygen corona contributes to source regions of high‐ and low‐energy escaping ions. Additionally, we present results for solar minimum and maximum conditions with respect to ion fluxes and energies in order to robustly describe the physical processes controlling planetary ion distributions and atmospheric escape.